The impact of downhill skiing on Galliformes and other birds - Mattia Brambilla; Francesca Roseo (Ecological Solutions and Evidence)
Abstract This work provides a systematic review of the impact of downhill skiing on birds. A literature search with no spatial and temporal restriction identified 48 documents in Web of Science and/or Scopus, which were used to investigate direct and indirect impacts of pistes and infrastructures, disturbances and other consequences on birds due to downhill skiing. Most of the studies were carried out in the Alpine region (especially in France, Italy, Switzerland and Germany). Only a few works explicitly assessed the impact of winter sports and ski‐lift cables on birds, mostly focusing on Galliformes, which are particularly sensitive to ski‐related impacts because of morphological, behavioural and ecological traits. Most studies assessing possible effects found a certain or very likely impact of ski‐lift cables and associated sport activities on birds, and especially on Galliformes. The difference in the number of studies reporting or suggesting impacts vs. those suggesting absence of effects was statistically different. There were very few results about mitigation approaches to limit the impact of ski‐lift cables on birds, and this prevents a clear and quantitative evaluation of the effectiveness of different types of visualisation/flagging systems used to make lift cables more visible to birds. In general, estimating the actual fatality rates, and thus the impacts of collisions and the effectiveness of possible mitigation tools, is very difficult and complicated due to sampling and detection issues. Practical implication. Ski resorts and related structures (cables in particular) impact birds, especially Galliformes. As the actual knowledge is insufficient to face the threats posed by downhill skiing, collision and possible mitigation measures, recreationist disturbance, habitat alteration, or possible creation of ecological traps represent key challenges for conservation and more research efforts are needed on those topics.